The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/w9080583
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Phosphorus Removal Structures: How to Assess and Compare Their Performance

Abstract: Controlling dissolved phosphorus (P) losses to surface waters is challenging as most conservation practices are only effective at preventing particulate P losses. As a result, P removal structures were developed to filter dissolved P from drainage water before reaching a water body. While many P removal structures with different P sorption materials (PSMs) have been constructed over the past two decades, there remains a need to evaluate their performances and compare on a normalized basis. The purpose of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 63 publications
1
74
0
1
Order By: Relevance
“…Much research is concerned with the effects of P removal by plants in wetlands [1,5,6], especially with the control of non-point source pollution [7]. However, plants can only absorb P in dissolved forms such as the free orthophosphate ions, H 2 PO 4 − and HPO 4 2− [8], while the available P in natural soil can be easily converted into insoluble complexes such as iron and aluminum hydrous oxides, crystalline and amorphous aluminum silicate, and calcium carbonate [9]. P can be dissolved by several mechanisms including Fe reduction [10], Ca removal and ligand exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Much research is concerned with the effects of P removal by plants in wetlands [1,5,6], especially with the control of non-point source pollution [7]. However, plants can only absorb P in dissolved forms such as the free orthophosphate ions, H 2 PO 4 − and HPO 4 2− [8], while the available P in natural soil can be easily converted into insoluble complexes such as iron and aluminum hydrous oxides, crystalline and amorphous aluminum silicate, and calcium carbonate [9]. P can be dissolved by several mechanisms including Fe reduction [10], Ca removal and ligand exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring and mitigation of stormwater from such developments should be treated as a priority water quality concern as well as a priority research topic. Practices such as the use of P sorbing materials in runoff detention/retention basins or P‐rich soils around poultry houses all show potential (Buda et al, 2012 Bryant et al, 2012; Penn et al, 2017). …”
Section: The Delmarva Peninsulamentioning
confidence: 99%
“…Water‐control structures can reduce SRP loss from fields by affecting hydrology (Evans et al, 1991; Penn et al, 2017; Zhang et al, 2017). Evans et al (1991) found a net reduction in edge‐of‐field total P losses of 35% under controlled drainage.…”
Section: Implementing Conservation Practices That Reduce Agriculturalmentioning
confidence: 99%
“…Phosphorus sorbing materials offer the potential to trap edge‐of‐field P losses when used in off‐site stormwater treatment structures. Off‐site structures that contained PSMs were found by multiple researchers (Penn et al, 2017; Qin and Shober, 2018) to be effective at removing soluble P (and to some extent particulate P) from runoff. Additionally, several researchers have demonstrated that PSMs in drain tiles may be useful in reducing leached P (King et al, 2016; McDowell et al, 2008).…”
Section: Implementing Conservation Practices That Reduce Agriculturalmentioning
confidence: 99%
See 1 more Smart Citation